Bed bug education for school, childcare center, and healthcare workers: Traditional versus webinar venues. Issue 1 (2nd January 2020) - Anderson, Marcia
Abstract: To protect the health and well-being of children and clients, workers in schools, childcare centers, and the healthcare industry need regular, state-of-the-art education on bed bug avoidance and control. For some, webinars provided by the United States Environmental Protection Agency are a convenient, free source of this education. Bed bug webinars were found to be as effective in conveying actionable information as traditional classroom-style workshops. Webinar audiences also grasped the bed bug prevention and control concepts as well as participants in classroom sessions. The study also documents the preferred education venue for each audience, the differences in attendance, and the environmental and cost savings afforded by webinars.